Synthesis of SnS2 modified to sulfated tin oxide by electrochemical method and VOC sensing properties - Sahin, Ayse Nur; Altindal, Ahmet; Ozdemir, Zeynep Guven (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2026)
This study investigates the room-temperature gas-sensing performance of next-generation sensors fabricated by electrochemically transforming 2D SnS2 films into SO42-/SnO2 structures. The sensors were prepared on an interdigital transducer via the spin-coating method, followed by low-potential electrochemical oxidation in a sulfuric acid-methanol medium to form a 3D SO42-/SnO2 structure. Unlike conventional high-temperature oxidation or chemical etching methods that cause bulk degradation, this study employs a low-potential electrochemical oxidation-sulfation strategy to controllably convert the SnS2 surface into SO42-/SnO2 while preserving the nano-structure. While the Sn core structure remained intact, FTIR, EDX, and XPS analyses confirmed the successful surface sulfation and the formation of sulfate-related chemical states on the SnO2 surface. XRD analysis verified crystalline-level structural transformation, and SEM imaging revealed distinct surface morphology changes. The gas-sensing performance was systematically evaluated against VOC's vapors over a concentration range of 50-350 ppm, enabling a comprehensive assessment of sensitivity and selectivity. Results showed that the SnS2-based sensor exhibited high sensitivity to acetone, whereas the SO42-/SnO2 structure demonstrated nearly tenfold enhanced responsiveness to NH3 vapor. Sulfate functionalization introduced Lewis acidic surface sites, strengthening interactions with NH3 and enabling nA-level responses. Although increased humidity (30-90 % RH) reduced response amplitude, reliable NH3 sensing was maintained, with interference tests at 50 % RH confirming robust performance. Furthermore, stable and repeatable signals over 10 days demonstrated excellent durability. These results highlight electrochemical surface engineering as an effective strategy to develop metal oxide-and chalcogenide-based NH3 sensors with improved selectivity, humidity tolerance, and long-term stability.
Keywords: SnS2; SO42-/SnO2; Electrochemical; VOC sensor; NH3; NANOSTRUCTURES; HETEROJUNCTION; FABRICATION; AMMONIA; Physics